Comparison of efficacy and safety of thrombus prevention strategies after abdominal and pelvic cancer surgery: Bayesian network based meta-analysis - Qin, Shiran; Guo, Sitong; Yao, Yucheng; He, Ying; Xu, Dandan; Su, Henghai; Chen, Xiaoyu; Meng, Haoru (Frontiers in Oncology, 2025)
BackgroundThe occurrence of venous thromboembolism (VTE) after abdominal and pelvic cancer surgery increases the risk of mortality and disability. However, there is insufficient evidence supporting the choice of anticoagulation strategies.MethodsWe searched PubMed, The Cochrane Library, Embase, and Web of Science for randomized controlled trials from inception to January 2024. Studies concerning thrombosis prevention after abdominal and pelvic surgery were included. Network meta-analysis(NMA) and direct meta-analysis (DMA) methods were employed to evaluate the efficacy and safety of various prophylactic strategies.ResultsTwenty clinical trials involving a total of 4923 patients were included. The DMA results showed that low molecular weight heparin (LMWH) was more effective in preventing VTE compared to no treatment (OR = 1.96; 95% CI: 1.21 to 3.19), and LMWH plus physiotherapy was more effective than LMWH (OR = 10.95; 95% CI: 1.33 to 90.40). The NMA results indicated that DOACs (OR = 0.34; 95% CI: 0.11 to 0.76) and LMWH (OR = 0.51; 95% CI: 0.32 to 0.77) were significantly effective in preventing venous thrombosis compared with no treatment. The cumulative ranking probability curve (SUCRA) showed that direct oral anticoagulants (DOACs) were the best intervention. In terms of major bleeding, unfractionated heparin (UFH) had a higher risk than LMWH, physiotherapy, and no treatment, with statistically significant differences. The SUCRA analysis indicated that physiotherapy was the best intervention for major bleeding.ConclusionExisting evidence suggests that DOACs can provide better thromboprophylaxis efficacy for patients after abdominal and pelvic cancer surgery, achieving an optimal balance between efficacy and safety. LMWH has become an intervention with efficacy second only to DOACs, with similar safety.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024513090.